1985
DOI: 10.2134/agronj1985.00021962007700050001x
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Root Distribution and Water Extraction Efficiency by Wheat Grown Under High‐ and Low‐Frequency Irrigation1

Abstract: A number of field experiments have separately evaluated plant responses to water stress, root distribution and soil water extraction patterns, consumptive water use, grain yield, and water use efficiency (WUE); few studies have investigated water movement through the soil‐plant‐atmosphere continuum as a whole. A field study was therefore conducted on spring wheat (Triticum aestivumL. cv. SST33), sown on a Rhodic Paleustalf soil in the Republic of South Africa, to relate the response of the plant and its root s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
38
0
3

Year Published

1989
1989
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(44 citation statements)
references
References 15 publications
3
38
0
3
Order By: Relevance
“…Effi ciency of irrigation water use in grain production would be improved if the plants develop better root systems before heading, even if shoot growth is suppressed to some extent. Much research on irrigation scheduling has been performed, but almost all studies involved fi xed irrigation intervals without consideration of the adaptive responses of plants to drought (Proffitt et al, 1985;Oweis et al, 1998Oweis et al, , 2000. However, it was reported recently that irrigation a few weeks before heading, during which roots grew vigorously, encouraged plants to develop shoots and roots more effectively with increased grain yield under severe soil moisture depletion (Xue et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Effi ciency of irrigation water use in grain production would be improved if the plants develop better root systems before heading, even if shoot growth is suppressed to some extent. Much research on irrigation scheduling has been performed, but almost all studies involved fi xed irrigation intervals without consideration of the adaptive responses of plants to drought (Proffitt et al, 1985;Oweis et al, 1998Oweis et al, , 2000. However, it was reported recently that irrigation a few weeks before heading, during which roots grew vigorously, encouraged plants to develop shoots and roots more effectively with increased grain yield under severe soil moisture depletion (Xue et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…It is important for the effi cient use of irrigation water and associated labor to determine how irrigation should be scheduled. Considerable researches have been conducted on the effects of drought stress and irrigation on wheat growth and yield (Proffitt et al, 1985;Kobata et al, 1992;Musick et al, 1994;Zhang et al, 1998;Oweis et al, 1998;2000;Foulkes et al, 2001;Yang et al, 2001;Xue et al, 2003). While soluble carbohydrate reserves before heading might contribute to grain yield to some extent (Yang et al, 2001;Foulkes et al, 2002), grain yield is mainly determined by dry matter production after heading (Schnyder, 1993;Gebbing and Schnyder, 1999).…”
mentioning
confidence: 99%
“…The development of root system can be promoted under moisture-defi cient conditions, even though it depends on the strength of the drought (Eghball and Maranville, 1993) and on both the species and the variety of plants Hida et al, 1995;Huang et al, 1997). A well-developed root system has also been reported in wheat plants grown under lower soil-moisture conditions (Proffi tt et al, 1985;Mian et al, 1993;Nakamura et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that, when soil moisture decreased, roots developed well especially in deeper soil, not only in the wheat (Box et al, 1989;Morita and Okuda, 1994;Proffitt et al, 1985) but also in soybean (Hida et al, 1995;Hirasawa et al, 1994Hirasawa et al, , 1998, cowpea, rice (Angus et al, 1983), peanut, millet (Inanaga et al, 1996), and other plants. Wheat roots in the shallower soil in the present experiment were not so long, as in earlier studies by others (Box et al, 1989;Box and Ramseur, 1993;Proffitt et al, 1985), perhaps due to the dry and compacted surface of the soil, light leakage and temperature effects, which resulted from insertion of the minirhizotron tubes (Wiesler and Horst, 1994;Smit et al, 2000). The resistance to water transport in plants in the D-plot, with their better-developed root systems, was smaller than that in the W-plot ( Table 3), indicating that plants in the D-plot had a greater capacity for water absorption (Hirasawa and Ishihara, 1991;Hirasawa et al, 1992a, b).…”
Section: Plotmentioning
confidence: 99%